2004
DOI: 10.1007/s00125-004-1340-8
|View full text |Cite
|
Sign up to set email alerts
|

Diabetic background retinopathy is associated with impaired coronary vasoreactivity in people with Type 1 diabetes

Abstract: Aims/hypothesis. We examined whether diabetic background retinopathy is associated with reduced coronary vasoreactivity in people with Type 1 diabetes. Methods. A total of 21 men with Type 1 diabetes were investigated, including 9 men with background retinopathy and 12 men without retinopathy. In addition, 12 non-diabetic, age-matched subjects were studied. All subjects were non-smokers, otherwise healthy and had no other diabetic complications. Resting myocardial blood flow and hyperaemic dipyridamole-stimula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
1

Year Published

2004
2004
2017
2017

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 32 publications
1
16
1
Order By: Relevance
“…However, studies with young type 1 diabetic subjects without complications have mainly shown normal coronary vasoreactivity [10,12,13,14]. The present study is the first study to examine the effect of hsCRP on coronary vasoreactivity in subjects with type 1 diabetes.…”
Section: Discussionmentioning
confidence: 72%
See 2 more Smart Citations
“…However, studies with young type 1 diabetic subjects without complications have mainly shown normal coronary vasoreactivity [10,12,13,14]. The present study is the first study to examine the effect of hsCRP on coronary vasoreactivity in subjects with type 1 diabetes.…”
Section: Discussionmentioning
confidence: 72%
“…In previous studies coronary vasoreactivity has been found to be decreased in diabetic patients with complications or other risk factors for coronary artery disease [7,8,9,11,12,13]. However, studies with young type 1 diabetic subjects without complications have mainly shown normal coronary vasoreactivity [10,12,13,14].…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Our findings are consistent with those from the Atherosclerosis Risk in Communities (ARIC) Study [7] and Cardiovascular Health Study [8], in which retinopathy lesions were associated with renal dysfunction. Retinopathy lesions are associated with abnormalities in the coronary circulation [23,24,25,26] and may thus be a marker of generalized microvascular disease from vascular endothelial dysfunction [27] in the retina, kidney and other microvascular beds.…”
Section: Discussionmentioning
confidence: 99%
“…Perfusion defects were noted in 16% of patients, and adenosine stress-induced ischemic electrocardiographic abnormalities or left ventricular dilation or dysfunction occurred in 6% of the patients with normal myocardial perfusion. Microvascular structural alterations affect coronary circulatory function more uniformly, judging from the homogenously reduced hyperemic flow patterns observed in patients with T2DM and diabetic retinopathy or coronary microangiopathy (19,20). Compared with controls, hyperemic myocardial flow was reduced by 28% in patients with T2DM and macrovascular coronary disease, but was reduced by 57% in patients with T2DM and coronary microangiopathy (20).…”
Section: Coronary Circulatory Function In States Of Irmentioning
confidence: 99%